NUTMEG: Open Source Software for M/EEG Source Reconstruction - Hinkley, Leighton B. N.; Dale, Corby L.; Cai, Chang; Zumer, Johanna; Dalal, Sarang; Findlay, Anne; Sekihara, Kensuke; Nagarajan, Srikantan S. (Frontiers in Neuroscience, 2020)
NUTMEG is an open-source MATLAB-based toolbox for the analysis and reconstruction of MEG/EEG data in source space. NUTMEG includes a variety of options for the user in data import, preprocessing, source reconstruction, and functional connectivity. A group analysis toolbox allows the user to run a variety of inferential statistics on their data in an easy-to-use GUI-driven format. Importantly, NUTMEG features an interactive five-dimensional data visualization platform. A key feature of NUTMEG is the availability of a large menu of interference cancellation and source reconstruction algorithms. Each NUTMEG operation acts as a stand-alone MATLAB function, allowing the package to be easily adaptable and scripted for the more advanced user for interoperability with other software toolboxes. Therefore, NUTMEG enables a wide range of users access to a complete “sensor-to- source-statistics” analysis pipeline.